PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI PADA KEPUTUSAN PEMBELIAN KONSUMEN TERHADAP PRODUK SAMBAL TENDO - Hariz Putra Arfianto; Febe Yuanita Ratna Indudewi (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
Abstract: The world of commerce today has increased various types of business that emerge in accordance with era development. Price determination, product quality and promotion that are done have to be accured. The purpose of this research is to analyze the effect of price, product quality and promotion variables on purchase decisions of Sambal Tendo consumer. The research that is used is with quantitative research. The measurement scaled uses Likert scale with data collection by using questionnaire. The analysis method that is used is with Multiple Linear Regression Analysis. The result shows that price affects significant on purchase decision, while product quality and promotion do not affected significant on purchase decision of Tendo consumers.